Pengembangan Buku Ajar Akidah Akhlaq Dengan Menggunakan Metode Inkuiri Pada Siswa kelas 2 di Madrasah Tsanawiyah Miftahul Ulum - Hosaini (Jurnal Pendidikan Islam, 2019)
Abstract: Islamic education learning is learning that has many roles in science, religion because be a role model all Muslims in the world. Besides, the Islamic religion can ensure the needs of the Islamic community life in this world and the Hereafter later. Therefore, it is important in the learning process of Islamic religious education, a teacher should have a lot of learning materials are varied and qualified in its implementation. One is a model of cooperative learning instructional materials in which a teacher is no longer a lecture in teaching but it was students who many propses an active role in learning and teaching. Long learning model needs to be updated in order to continue learning to walk properly and in accordance with the demands of the future will face the students later. Change is inevitable again, vorefer into the demands of the Islamic Ummah , but the changes are not out of the rules of the teachings of Islam that has taught him. That is why it is possible learning materials provides opportunities for Islamic religious education teachers to always be active in the learning process according to their individual needs lembanga Islamic education. This study focused on how the effectiveness of Islamic religious education learning materials with a model inkuiru? Certainly address this problem requires a learning model that can please the students learn continuously to obtain the expected results. Students will not be able to learn seriously as long as there is no motivation given the teacher to the students, so it turned out not to be enough wit a science teacher who had qualified without having learning models that support. One satuya to the spirit of learning that encourages students to learn is a model Inkuiri .